Measuring the Performance of Corporate Acquisitions: An Empirical Comparison of Alternative Metrics - Schoenberg, Richard (Blackwell Publishing Ltd, 2006)
The choice of performance measure has long been a difficult issue facing researchers. This article investigates the comparability of four common measures of acquisition performance: cumulative abnormal returns, managers' assessments, divestment data and expert informants' assessments. Independently each of these measures indicated a mean acquisition success rate of between 44–56%, within a sample of British cross-border acquisitions. However, with the exception of a positive relationship between managers' and expert informants' subjective assessments, no significant correlation was found between the performance data generated by the alternative metrics. In particular, ex-ante capital market reactions to an acquisition announcement exhibited little relation to corporate managers' ex-post assessment. This is seen to reflect the information asymmetry that can exist between investors and company management, particularly regarding implementation aspects. Overall, the results suggest that future acquisitions studies should consider employing multiple performance measures in order to gain a holistic view of outcome, while in the longer term, opportunities remain to identify and refine improved metric